A política curricular de ciclos no município de Campina Grande: análise dos sentidos e efeitos da avaliação no contexto da prática - Souza, Maria das Vitórias B. de (2016)
The evaluation, while educational policy has gained in recent years centrality as an essential tool to the quality of teaching in social and managerial perspective, showing up in this last one as a strong government control mechanism to promote what Ball (2001) called "joint government". Recognizing the educational policy while complex area of different interests and dispute seems urgent to bring to analysis one of the alternative policies to the ones released by the official field. Linked to the research educational policies of the Programa de Pós-Graduação em Educação – PPGE from Universidade Federal da Paraíba -UFPB, this dissertation analyzes the process of Curricular policy recontextualization of cycles in the city of Campina Grande-PB focusing on the senses and effects that the proposed evaluation presented by this policy brought to the context of practice. Before the invitation to reflection about the formative character of the evaluation released by Cycles as opposed to official requirements focused on results fit the following questions: What needs led this municipality to adopt the policy cycles and under what assumptions? What guidelines for evaluation were considered in the political text and how they were translated under secretary of education, school and teaching practice? To answer such questions it was launched as general objective: investigate the meanings and effects of the implementation of the policy of cycles in the city of Campina Grande, focusing on evaluative practices, in two elementary schools II, in the period from 1999 to 2015. The methodological route was based on the qualitative approach and adopted as the analytical reference policy cycles approach of Stephen Ball on reinterpretation of the contexts of influence, of preparation of texts and of the context of practice. The empirical field of this research have configured into two schools that work with the final years of elementary school (III and IV cycles) and the Municipal Secretary of Education. The data collection occurred through documentary analysis and semi-structured interviews carried out with 15 (fifteen) teachers of the III and IV cycles, 02 (two) school managers and with the Manager of elementary school. The analysis of the interviews was organized in three categories, which results showed that despite 15 years of existence, the adoption of the cycles has failed to promote a substantial change in their functioning demonstrating to be tied exclusively to the practice of do not fail. The speeches about the meanings assigned to evaluation were antagonistic: At the same time that they recognized it as essential to the forming practice, they revealed practices needs linked to the traditional paradigm by pointing the school failure as the main potential to learning. The lack of training and resistance observed in part of respondents added to financing to provide better working conditions and the requirements of current educational policies were the main reasons to return to serial organization. The adoption of evaluation system based on obligation to use tests and arithmetic average came to be understood as potentiality to the vaunted guarantee of learning rights of students, leaving us waiting under the following question: Have we taken a step behind or a step forward?